Antibacterial Activity Of Ethanol Extract And Methanol Extract Of Guava Leaves (Psidium guajava L.) Againts Staphylococcus aureus - Kurniaty, Rina; Dewi , Resmila; Yusup, Muhilal (Universitas Negeri Medan, 2025)
Guava leaves contain secondary metabolites, consisting of tannins, polyphenolates, flavonoids, monoterpenoids, alcolloids, quinones, and saponins. The main component of guava leaves is tannins, the amount of which reaches 9-12%. Tannins are antibacterial by precipitating proteins. The antimicrobial effect of tannins is through reactions with cell membranes, inactivation of the function of genetic material. alkaloids, flavonoids can inhibit the growth of Staphylococcus aureus. This research aims to find out the activities antibacterial ethanol and methanol extract of guava leaves against Staphylococcus aureus. This study uses the disc diffusion method. Using 5 treatment groups, namely positive control using chlorampenicol antibiotics and for positive control using DMSO. For concentrations of 5%, 10%, 15% use ethanol extract and methanol guava leaves. This study is an experimental study, testing antibacterial activity using Staphylococcus aureus bacteria. The data obtained was analyzed using the One Way ANOVA test and continued with the DMRT/Ducan test to see the difference in each treatment. The average results of the diameter of the inhibition zone for ethanol extracts were 10.47 mm (5%), 11.95 mm (10%), 16.94 mm (15%). For methanol extracts it is 9.7 mm (5%), 12.1 mm (10%), 19.7 mm (15%). One Way ANOVA analysis followed by DMRT/Ducan showed that both shallot extracts have antibacterial potential and do not have significant differences. The conclusion of this study is that guava leaf ethanol and methanol extracts with concentrations of 5%,10% and 15% have potential as antibacterial against Staphylococcus aureus.